The Contribution of Immune and Glial Cell Types in Experimental Autoimmune Encephalomyelitis and Multiple Sclerosis - Duffy, Samuel S.; Moalem-Taylor, Gila; Lees, Justin G. (Multiple Sclerosis International, 2014)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system characterised by widespread areas of focal demyelination. Its aetiology and pathogenesis remain unclear despite substantial insights gained through studies of animal models, most notably experimental autoimmune encephalomyelitis (EAE). MS is widely believed to be immune-mediated and pathologically attributable to myelin-specific autoreactive CD4+ T cells. In recent years, MS research has expanded beyond its focus on CD4+ T cells to recognise the contributions of multiple immune and glial cell types to the development, progression, and amelioration of the disease. This review summarises evidence of T and B lymphocyte, natural killer cell, macrophage/microglial, astrocytic, and oligodendroglial involvement in both EAE and MS and the intercommunication and influence of each cell subset in the inflammatory process. Despite important advances in the understanding of the involvement of these cell types in MS, many questions still remain regarding the various subsets within each cell population and their exact contribution to different stages of the disease.